Prevalence of and Risk Factors for Anal Human Papillomavirus Infection in a Sample of Young, Predominantly Black Men Who Have Sex With Men, Houston, Texas. (5th December 2017) - Nyitray, Alan G; Fujimoto, Kayo; Zhao, Jing; Giuliano, Anna R; Schneider, John A; Hwang, Lu-Yu
Abstract : Approximately two thirds of a sample of predominantly black men who have sex with men harbored human papillomavirus (HPV) genotypes in the anal canal that most commonly cause malignant and nonmalignant disease. It is important to increase the currently low HPV vaccine coverage in this population. Abstract: Background: Young men who have sex with men (MSM) are at increased risk for human papillomavirus (HPV)–associated disease as a result of HPV infection. Our objective was to characterize the prevalence of high-risk anal HPV infection and factors associated with prevalence in a group of young, primarily black MSM in Houston, Texas. Methods: MSM aged 18–29 years were recruited using a respondent-driven sampling method to study HIV and sexually transmitted disease transmission and risk. All engaged in peer-recruitment chains and self-collected anal exfoliated cells. Prevalence ratios assessed factors associated with high-risk HPV and HPV types in the 9-valent vaccine. Results: Black race was reported by 87% of men. Slightly over one half (53%) were human immunodeficiency virus (HIV) positive. Approximately 75% of men had at least 1 high-risk HPV type, and 39% of HIV-positive men harbored HPV-16. Analysis that controlled for potential confounders revealed that only HIV infection was associated with high-risk HPV infection. Conclusion: Black MSM would benefit from increased HPV vaccination efforts, owing to high rates of HPV infection, increased HPV disease, and low vaccination series completion rates in this population.